2011
DOI: 10.1016/j.chom.2011.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Transfer of HIV-1 via Virological Synapses Leads to Endosomal Virion Maturation that Activates Viral Membrane Fusion

Abstract: SUMMARY HIV-1 can infect T cells by cell-free virus or by direct virion transfer between cells through cell contact-induced structures called virological synapses (VS). During VS-mediated infection, virions accumulate within target cell endosomes. We show that after crossing the VS, the transferred virus undergoes both maturation and viral membrane fusion. Following VS transfer, viral membrane fusion occurs with delayed kinetics and transferred virions display reduced sensitivity to patient antisera compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
152
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(170 citation statements)
references
References 34 publications
(56 reference statements)
14
152
3
1
Order By: Relevance
“…In an interesting twist, Melikyan and co-workers (62) found that hemifusion occurred at the plasma membrane but that pore expansion occurred following endocytosis in the endosome. Although the endocytic pathway was revealed by observation on the micrometer scale (62,63), it was not supported by examination on the nanoscale in primary lymphocytes (64). Inhibitors of dynaminand clathrin-dependent endocytosis (62,65) have been invoked to argue for HIV entry via endocytosis, but such inhibitors have multifaceted effects on cellular processes, including cell-cell fusion (66).…”
Section: Microscale Determination Of the Hiv Fusion Cascadementioning
confidence: 99%
“…In an interesting twist, Melikyan and co-workers (62) found that hemifusion occurred at the plasma membrane but that pore expansion occurred following endocytosis in the endosome. Although the endocytic pathway was revealed by observation on the micrometer scale (62,63), it was not supported by examination on the nanoscale in primary lymphocytes (64). Inhibitors of dynaminand clathrin-dependent endocytosis (62,65) have been invoked to argue for HIV entry via endocytosis, but such inhibitors have multifaceted effects on cellular processes, including cell-cell fusion (66).…”
Section: Microscale Determination Of the Hiv Fusion Cascadementioning
confidence: 99%
“…In addition, HIV-1 particles transmitted through virological synapses could, at least temporarily, be attached to both cells across the contact area (88). The fact that cell-to-cell transmission does not normally lead to cell fusion suggests negative regulation of this entry pathway, perhaps through delayed virus maturation (89) or through host factors interfering with the fusion process (90,91). If complete HIV-1 fusion at the cell surface relies on actin, what drives pore dilation in endosomes following CD4-and coreceptor-mediated uptake?…”
Section: Hiv-cell and Hiv-mediated Cell-cell Fusion Are Differentlymentioning
confidence: 99%
“…De même, on ne connaît pas les mécanismes précis d'entrée du virus HTLV-1 dans la cellule cible lors de la transmission synaptique, ou lors du transfert de biofilm. Y a-t-il fusion à la membrane, ou, comme dans le cas du VIH-1, endocytose des particules virales et fusion dans les endosomes [45] ? Enfin, la nécessité d'un contact étroit entre une cellule infectée et sa cible suggère que le succès de l'infection pourrait aussi dépendre de signaux complémentaires induits par l'engagement de protéines cellulaires au moment du contact.…”
Section: Les Conduits : Réseaux Facilitant La Transmissionunclassified